1998
DOI: 10.1038/30400
|View full text |Cite
|
Sign up to set email alerts
|

Role of a p53 polymorphism in the development of human papilloma-virus-associated cancer

Abstract: The E6 oncoprotein derived from tumour-associated human papillomaviruses (HPVs) binds to and induces the degradation of the cellular tumour-suppressor protein p53. A common polymorphism that occurs in the p53 amino-acid sequence results in the presence of either a proline or an arginine at position 72. The effect of this polymorphism on the susceptibility of p53 to E6-mediated degradation has been investigated and the arginine form of p53 was found to be significantly more susceptible than the proline form. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
709
12
36

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 876 publications
(780 citation statements)
references
References 37 publications
23
709
12
36
Order By: Relevance
“…Furthermore, there was a statistically significant dose‐dependent relationship for TP53 G72C genotypes (Cochran‐Armitage trend test, P  = .011), indicating an ordering in the effect of the G allele in HPV‐positive patients. In fact, it is this allele that is deemed more prone to degradation by high‐risk HPV‐E6 oncoprotein 10. Consistent with our results, Hu et al21 also reported that the TP53 G72 (Arg) was significantly overtransmitted in Caucasian CxCa subjects of a family‐based association study where HPV was determined, especially in subjects who were infected with HPV16/18 21.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, there was a statistically significant dose‐dependent relationship for TP53 G72C genotypes (Cochran‐Armitage trend test, P  = .011), indicating an ordering in the effect of the G allele in HPV‐positive patients. In fact, it is this allele that is deemed more prone to degradation by high‐risk HPV‐E6 oncoprotein 10. Consistent with our results, Hu et al21 also reported that the TP53 G72 (Arg) was significantly overtransmitted in Caucasian CxCa subjects of a family‐based association study where HPV was determined, especially in subjects who were infected with HPV16/18 21.…”
Section: Discussionsupporting
confidence: 90%
“…Following the first description of the potential usefulness of the Arg genotype as a marker of risk to develop uterine cervix neoplasia,10 there were many studies that examined the association between CxCa and TP53 G72C SNP; however, the results in various populations were inconsistent 21. Nevertheless, there is substantial collective evidence to support a sound association specifically when HPV status is considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The replacement of proline with arginine abolishes one of the ®ve PXXP motifs. Recently it has been reported that the p53 Arg is signi®cantly more susceptible than p53 Pro to E6-mediated degradation to human papilloma virus (HPV)-induced tumours in homozygous p53 Arg (Storey et al, 1998). This correlates with the clinical ®nding that individuals homozygous for Arginine 72 are more susceptible to human papillomavirus associated tumorigenesis than heterozygotes, at least in certain populations (Storey et al, 1998).…”
Section: Amino-terminal Region Of P53mentioning
confidence: 99%
“…Although deletion of the proline-rich domain does not a ect transactivation of several promoters, such as WAF1, mdm2 and BAX, it does alter transcriptional repression (Venot et al, 1998). A chief point of interest is the fact that p53 gene is polymorphic at amino acid 72 which results in either a proline (p53 Pro) or a arginine (p53 Arg) at this position (Storey et al, 1998). The replacement of proline with arginine abolishes one of the ®ve PXXP motifs.…”
Section: Amino-terminal Region Of P53mentioning
confidence: 99%